1986
DOI: 10.1002/ijc.2910380618
|View full text |Cite
|
Sign up to set email alerts
|

EBV‐negative and ‐positive burkitt cell lines variably express receptors for B‐cell activation and differentiation

Abstract: The expression of receptors for proliferation and differentiation factors was analyzed by indirect immunofluorescence on 29 Burkitt lymphoma (BL) cell lines previously classified into 3 groups on the basis of their reactivity with 8 monoclonal antibodies (MAbs), including anti-CALLA, BL13 and TU1. BL13 and HB5 antibodies recognize different epitopes of the EBV/CR2 receptors. The determinant recognized by BL13 has been previously shown to be expressed only on cell lines of the first two groups, supposed to deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…BL lines that have been propagated in vitro for a prolonged period of time are heterogeneous with regard to expression of B-cell activation and differentiation markers (Rowe et al, 1986;Favrot et al, 1986) and, in the case of EBV-carrying BLs, viral antigens (Rowe et al, 1987). EBV-negative BL lines, and some of the EBV-positive ones, maintain the phenotype of the biopsy cells characterized by high expression of CDlO and CD77, absence of B-cell activation markers and down-regulation of all EBV-encoded antigens except EBNA-1 (group-I BLs).…”
Section: Discussionmentioning
confidence: 99%
“…BL lines that have been propagated in vitro for a prolonged period of time are heterogeneous with regard to expression of B-cell activation and differentiation markers (Rowe et al, 1986;Favrot et al, 1986) and, in the case of EBV-carrying BLs, viral antigens (Rowe et al, 1987). EBV-negative BL lines, and some of the EBV-positive ones, maintain the phenotype of the biopsy cells characterized by high expression of CDlO and CD77, absence of B-cell activation markers and down-regulation of all EBV-encoded antigens except EBNA-1 (group-I BLs).…”
Section: Discussionmentioning
confidence: 99%
“…A major obstacle in this regard has been the lack of any clear definition of the particular B cell subset from which the tumour is derived. Many attempts have been made to define the cell surface phenotype of the tumour by analyzing BL cell lines, often long after their establishment in vitro, but these studies have invariably found that such lines display any one of a range of different phenotypes (Nilsson and Klein, 1982;Favrot et al, 1984;Ehlin-Henriksson and Klein, 1984;Favrot et al, 1986;Cohen et al, 1987). Accordingly this has fostered the view that BL can arise from target cells at any one of several positions along the B cell differentiation pathway.…”
Section: Isolation Of a Normal B Cell Subset With A Burkitt-like Phenmentioning
confidence: 99%
“…The positivity for CD21 demonstrates, in addition, the presence of Epstein-Barr virus receptors on these cells. The CD77 marker has been hitherto described in Burkitt's lymphoma (BL) cell lines, but not lymphoblastoid cell lines (LCLs) growing out of healthy individuals seropositive for EpsteinBan" virus (Favrot et al, 1986;Rooney et al, 1986;Cohen et al, 1987;Avila-Carino et al, 1991). However, we found that CD77 antiserum obtained from Serotech reacted also with LCLs obtained from the peripheral blood of two immunosuppressed organ transplant recipients without posttransplant lymphoproliferative disease.…”
Section: Discussionmentioning
confidence: 55%